Factors Associated with Colorectal Cancer Diagnosis Compared to Other Digestive Cancers at the National Cancer Control Center of Niamey (Niger), 2018–2023: A Hospital-Based Analytical Study - Mohamed, Fatima; Barikissou Georgia, Damien; Salifou Ibrahim, Alkassoum; Soumaila, Amadou; Aguemon, Badirou (European Scientific Journal, ESJ, 2026)
Introduction: Colorectal cancer (CRC) is a major public health concern, with a rising incidence in low- and middle-income countries, particularly in sub-Saharan Africa. In Niger, data on factors associated with CRC are limited. This study aimed to identify sociodemographic, socioeconomic, clinical, and behavioral factors associated with colorectal cancer diagnosis compared to other digestive cancers in a hospital-based population. Methods: This retrospective analytical study was conducted at the National Cancer Control Center (CNLC) of Niamey, including patients with histologically confirmed digestive cancers between January 1, 2018, and December 31, 2023. Associations between CRC diagnosis and independent variables were assessed using bivariate analyses (χ² or Fisher’s exact test), followed by multivariate logistic regression for variables with p < 0.20. Adjusted odds ratios (ORs) with 95 % confidence intervals (CI) were calculated. Verbal informed consent was obtained from participants or their relatives during telephone interviews, especially for patients whose vital status was unknown from medical records. Results: A total of 433 digestive cancer cases were initially identified, including 231 colorectal cancers and 202 other digestive cancers. After exclusion of 9 incomplete CRC records, 424 cases were included in the final analysis (222 CRC and 202 non-CRC). The mean age was 48.6 ± 15.4 years, with a male predominance (62.2 %). In multivariate analysis, Lack of income was significantly associated with CRC diagnosis (OR = 4.85; 95 % CI: 1.40–16.00; p = 0.014). A consultation delay of two years or more was also significantly associated with hospital-diagnosed colorectal cancer (OR = 4.05; 95 % CI: 1.90–18.00; p = 0.034). Behavioral factors (tobacco, alcohol, obesity) and family history of CRC were not independently associated with colorectal cancer diagnosis. Conclusion: Colorectal cancer accounted for a substantial proportion of digestive cancers in this hospital-based study. Patients with colorectal cancer were more likely to present with low socioeconomic status and prolonged consultation delays compared to those with other digestive cancers. These findings highlight disparities in access to care and diagnostic pathways rather than etiological risk factors. Strengthening early detection, community awareness, and financial accessibility to care may help improve patient management and outcomes in Niger.